Il vincolo simbolico tra uomo e natura - Poma, Iolanda (Filosofia, 2019)
Beginning from the consideration of the ecological and environmental emergency, this article examines the dynamics of man’s relationship with nature. The sense of their interdependence is irreducible to simple human survival and natural self-preservation: human freedom recognizes in natural necessity a model able to limit human congenital defect that is arbitrariness; and, illuminated by freedom, nature reveals a face of its necessity, which is able to get in dialogue with freedom. Their mutual connection is therefore reformulated in terms of symbolic link. It is possible to find examples of symbolic bond in Jean-Jacques Rousseau’s relationship with nature, in its various forms, and with interesting links to contemporary philosophy. The path finally opens up to a reflection on the role of the body, as a turning point between nature and culture.